WANITA SALAT BERJAMAAH DI MASJID (Kajian Teori Double Movement Terhadap Ayat 33 Surah Al-ahzab dan Nash-Nash Terkait) - Al Yasa’ Abubakar; Muhammad Agus Andika (Universitas Islam Negeri Ar-Raniry, 2019)
The problem of leaving a woman from home for various activities is prohibited in the Qur'an surah al-Ahzab verse 33 if it is understood in general. It is also stated in the hadith narrated by ibn khuzaimah that a woman is aurat who should not go out, especially without someone accompanying her. But there is another hadith narrated from Abu Hurairah which states that a husband should not prohibit his wife from approaching the house of Allah. Then how is the law of women praying in congregation in mosques based on the Double Movement Theory against verse 33 of surah al-Ahzab and related passages. The research method used in this paper is Library Research. In the case of women praying in congregation in mosques, the clause regarding elevating the status of women and giving women the opportunity to participate in public spaces must receive attention and be determined to have fundamental interests. Furthermore, through the double movement theory It can be understood that in this case, the Qur'an intends to maximize equality between men and women, and for this purpose it states that a woman's freedom in the public sphere is normally ideal.